FISCAL DECENTRALIZATION AND LOCAL BUSINESS DEVELOPMENT: THE ROLE OF REGIONAL TAX POLICIES IN ECONOMIC GROWTH - Loso Judijanto; Muthmainnah Muthmainnah; Puteri Aprilani (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the impact of fiscal decentralization on local business development through the implementation of regional tax policies to encourage economic growth. Fiscal decentralization provides greater authority to regional governments in managing revenue sources and determining fiscal policies according to the characteristics of their respective regions. In the context of regional economic development, regional tax policies are a strategic instrument that can create a conducive business climate, increase investment, expand employment opportunities, and strengthen local economic competitiveness. This study uses a literature review method by examining various scientific articles, academic books, policy reports, and previous research results related to fiscal decentralization, regional tax policies, local business development, and economic growth. The results of the study indicate that fiscal decentralization can have a positive impact on regional economic growth when accompanied by effective, transparent, and accountable fiscal governance. Regional tax policies that are proportional and oriented towards business development have been proven to increase local economic activity, particularly in the micro, small, and medium enterprise sector. In addition, the flexibility of regional governments in determining fiscal incentives also contributes to increased investment and economic productivity. However, this study also identified challenges in the form of disparities in fiscal capacity between regions, low effectiveness of regional tax administration, and the potential for excessive tax burdens on businesses. Therefore, synergy between the central and regional governments is needed to formulate adaptive and sustainable fiscal policies to create inclusive and equitable economic growth.